The Development of an Environment Problem Based Module on Environmental Change Material for High School Students - Dewi, Rizqi Mareta; Ngabekti, Sri (FMIPA UNNES, 2021)
This research aims to analyze the validity, the readability, and the effectiveness of the environment problem based module on environmental change subject for high school students. This research was conducted at SMA Negeri 3 Brebes on the second semester in the Academic Year of 2019/2020. The design of this research is Research and Development (R&D). The population of this research is the class of X MIPA 5 SMA Negeri 3 Brebes. The sample of this study is 10 students of X MIPA 5 class that was chosen by using purposive sampling technique. The result of this study showed that the average of the validity value of the environment problem based module by subject and media experts is 90,71 with the criteria is very valid. The readability value by the teacher is 96,25 and by the students is 87,25 with the criteria is very good. The accumulated effectiveness test score of 83.5 is included in the very effective category. The effectiveness test of cognitive aspects showed that 90% of the students have a score above 70, the result of the psychomotor aspects showed that 7 students have a very good problem solving skills and 3 students have a good problem solving skills, and the result of the affective aspects showed that 70% of the students have a very high environmental care attitude and 30% of the students have a high environmental care attitude. The conclusion of this study is the environment problem based module is feasible and effectively used to help the students learn independently and as a source of additional learning for students.